Strategi Relationship Marketing dalam Membangun Loyalitas Pelanggan Pada PT Pantero Selaras Agung Jakarta - Lukman; Ririn (LPPM Universitas Bina Sarana Informatika, 2024)
PT Pantero Selaras Agung is a business entity or organization that operates in the field of providing goods and services related to information technology (IT) for its clients or consumers. Of course, by providing good service, there is a need for a strategy or way to achieve the company's goals. One of the strategies used is to establish good relationships with users of goods/services, namely customers, therefore establishing good relationships with customers is an important thing to do. build loyalty and retain customers. This research aims to determine the relationship marketing strategies implemented as an effort to building customer loyalty at PT Pantero Selaras Agung Jakarta. The supporting theory used is interpersonal communication theory in forming and maintaining relationships with customers. The method used in this research is a qualitative descriptive research method with field research and data collection methods, namely interviews, observation and documentation. The relationship marketing strategy used to build customer loyalty is by analyzing customer needs, establishing cooperation (partnerships). The success of using a relationship marketing strategy can be seen from customer loyalty, namely by having customers who are willing to spread positive information and make repeat purchases.